Lithic technographies of the middle holocene in the central region of South America: cultural tesserae for a paleo-historical mosaic (second part) - de M. Ramos, Marcos Paulo; Carbonelli, Juan Pablo; Viana, Sibeli A.; Costa, Kaira S. R. (Facultad de Filosofía y Humanidades. Museo de Antropología, 2023)
This article constitutes the second part of the lithic technographic analysis of Middle Holocene sites in a vast macro-region, the central portion of South America: it includes the groups of sites B, C and D. A common element in all the analyzed sets is the presence of the techno-functional category B tools. In reference to the production mode, it is observed that the principle of debitage predominates in the area of analysis. However, its application was diverse; there are assemblages in which there was a predetermination about the making of flakes, others in which the cores were reintroduced as blanks or presented edges and there are other places in which façonnage confection flakes were reintroduced as blanks for tools. Other production principles have also been recorded: the principles of affordance (both in the exclusive productional expression and in its productional and functional expression) and shaping are observed in sites in groups A, C and D. Recognizing the different production modes is the starting point for thinking about how groups with different technical traditions have occupied different spaces in the region.